2017
DOI: 10.4037/ajcc2017510
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence at First Cardiopulmonary Resuscitation and Subsequent Limitations on Care in the Medical Intensive Care Unit

Abstract: For unclear reasons, family-witnessed CPR in the medical intensive care unit is associated with a similar rate of subsequent CPR efforts and lower rates of return of spontaneous circulation and survival to hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…[388][389][390][391][392]399,404,406,407,411,414,416 Four studies compared family presence with no family presence. [388][389][390]404 Only 1 study found higher rates of ROSC and survival to discharge when no family members were present during resuscitation. 389 2.…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…[388][389][390][391][392]399,404,406,407,411,414,416 Four studies compared family presence with no family presence. [388][389][390]404 Only 1 study found higher rates of ROSC and survival to discharge when no family members were present during resuscitation. 389 2.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…[388][389][390]404 Only 1 study found higher rates of ROSC and survival to discharge when no family members were present during resuscitation. 389 2. Family outcomes were reported in 15 studies 387,388,[391][392][393][394][395]403,[405][406][407][408]411,414,416 investigating depression, anxiety, posttraumatic stress disorder, and experience of witnessing the resuscitation of a family member.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Family presence has also been preferred by patients who have gone through cardiac resuscitation (Bradley, Keithline, Petrocelli, Scanlon & Parkosewich, 2017;Krochmal et al, 2017). Our review highlighted the moderate quality of evidence to demonstrate the impact of family presence in rounds on family and patient-centered outcomes.…”
Section: Interaction and Communicationmentioning
confidence: 94%
“…104 A retrospective study of more than 300 patients in a medical intensive care unit showed significantly lower rates of return of spontaneous circulation and survival to hospital discharge for patients whose families were present during cardiopulmonary resuscitation. 105 Although these results are not consistent across studies, they do raise an important issue. While humanization is innately right, it does not necessarily follow that all efforts to optimize it should be pursued without considering the risk-benefit balance.…”
Section: Quantitative Outcomes Addressedmentioning
confidence: 87%